Electrolyzed Water Generated On-Site as a Promising Disinfectant in the Dental Office During the COVID-19 Pandemic - Farah, Ra'fat Ibrahim; Al-Haj Ali, Sanaa Najeh (Frontiers in Public Health, 2021)
Electrolyzed water is a safe, broad-spectrum bactericidal and viricidal agent, which can be used as a potent and effective alternative disinfectant in case of supply shortages. This report describes the on-site production of slightly acidic electrolyzed water (EW) from diluted salt solution and vinegar at a dental office using a portable EW generator unit. Such measures can ensure safe continuity of important dental service provision for our patients during the coronavirus disease 2019 (CoVID-19) pandemic.